Double prosthesis in the treatment of inguinal hernia: a new concept - Croci, Fabio; Tacain, Gustavo (Cirugía del Uruguay, 2000)
Previous repair of inguinal hernia treated on/y the presence of the defect or ignored the defect and treated ali the inguinal wa/1. But it is /ogical to think that simultaneous treatment of both situations could /ead to better results with an even greater reduction in reherniation index highly significant at present).